The role of natural products targeting macrophage polarization in sepsis-induced lung injury - Yake Li; Sinan Ai; Yuan Li; Wangyu Ye; Rui Li; Xiaolong Xu; Qingquan Liu (Chinese Medicine)
Abstract Sepsis-induced acute lung injury (SALI) is characterized by a dysregulated inflammatory and immune response. As a key component of the innate immune system, macrophages play a vital role in SALI, in which a macrophage phenotype imbalance caused by an increase in M1 macrophages or a decrease in M2 macrophages is common. Despite significant advances in SALI research, effective drug therapies are still lacking. Therefore, the development of new treatments for SALI is urgently needed. An increasing number of studies suggest that natural products (NPs) can alleviate SALI by modulating macrophage polarization through various targets and pathways. This review examines the regulatory mechanisms of macrophage polarization and their involvement in the progression of SALI. It highlights how NPs mitigate macrophage imbalances to alleviate SALI, focusing on key signaling pathways such as PI3K/AKT, TLR4/NF-κB, JAK/STAT, IRF, HIF, NRF2, HMGB1, TREM2, PKM2, and exosome-mediated signaling. NPs influencing macrophage polarization are classified into five groups: terpenoids, polyphenols, alkaloids, flavonoids, and others. This work provides valuable insights into the therapeutic potential of NPs in targeting macrophage polarization to treat SALI. Graphical Abstract